Legal Updates on the Reporting System for Violence Against Women and Children through Strengthening Victim Protection Mechanisms Based on Access to Justice and a Victim-Centered Approach - Riyan Permana Putra; Zulkarnein Koto; Kif Aminanto (Journal Customary Law, 2026)
This study aims to analyze the minimal reporting of victims of violence against women and children in the legal protection system in Indonesia and to formulate legal reforms to the reporting system based on access to justice and a victim-centered approach. The research problem stems from the high number of violence against women and children that is not proportional to the number of reports received by law enforcement officials due to weak victim protection, a culture of victim blaming, victim trauma, power relations, low gender sensitivity of officials, and a reporting system that is not yet integrated and not based on a trauma-informed approach. This study uses a normative juridical method with a legislative approach and a conceptual approach through a study of the 1945 Constitution of the Republic of Indonesia, the Law on the Crime of Sexual Violence, the Child Protection Law, the Law on the Elimination of Domestic Violence, the Law on the Protection of Witnesses and Victims, and various international legal instruments such as CEDAW and CRC. The results of the study indicate that the Indonesian criminal law system still tends to be offender-oriented, with victims not recognized as the primary subjects of legal protection. Therefore, legal reform is needed through the development of an integrated victim protection mechanism based on a digital reporting system, a trauma-informed reporting system, automated identity protection, mandatory legal and psychological assistance, strengthening the Women's Empowerment and Child Protection Unit (PPA) and the Witness and Victim Protection Agency (LPSK), and the implementation of victim-centered justice to create a reporting system that is more responsive, safe, inclusive, and oriented toward victim recovery and human rights protection.